THE BANDWAGON EFFECT OF A SIMPLE CANDIDATE PREFERENCE MODEL AS A MODEL OF POLITICAL EDUCATION COMMUNICATION - Hasibuan, Iskandar Muda; Morissan, Morissan; Purnomo, Marlinda Irwanti (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Purpose: This study aims to analyze the influence of political communication strategy models, namely the bandwagon effect, expected utility, and simple candidate preferences partially on voters' voting decisions, as well as to analyze the similarities and differences in the effectiveness of implementing these political communication strategy models among the three candidate pairs. Method: The research approach is quantitative. The population is the millennial generation of Indonesian citizens (WNI) registered on the Permanent Voter List (DPT) in DKI Jakarta Province who have characteristics as millennials, voted in the presidential election on February 14, 2024, and before the election day had the opportunity to participate in the political communication of the three presidential candidates through social media platforms. The sampling technique is purposive sampling. Secondary data collection techniques through study desks, while primary data collection techniques through survey and interview methods. The data analysis technique uses Structural Equation Modeling Partial Least Square (SEM-PLS). Result: The results of the study indicate that the simple candidate preference model has a significant influence in shaping people's political choices through social imitation mechanisms and perceptions of candidate popularity. Conclusion: The bandwagon effect that emerges can increase political participation and awareness of the democratic process, but also has the potential to reduce the quality of political rationality if it is not balanced with critical political education.